Recreational road runners: injuries, training, demographics and physical characteristics - Joris Pazin; Maria de Fátima da Silva Duarte; Lisiane Schilling Poeta; Marcius de Almeida Gomes (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n3p277 The purpose of this study was to study recreational road runners in order to identify: their physical characteristics, demographics, running profile (training distance, frequency, duration, and experience) and the prevalence of injuries and their association with age, running profile, and other sports practiced. Body mass, height (from which BMI was calculated) and waist circumference were also measured. The sample of runners was composed of 115 men who participated in two events organized in Santa Catarina State, Brazil, in 2006: 22nd Maratona de Blumenau and 5th Desafio Praias e Trilhas (Florianópolis). The data were analyzed with descriptive statistics and the chi-square test to identify associations between injury prevalence and other variables (p<.05). The majority of the runners were aged between 18 and 50 years (63.2%), with 36.8% older than 50 years. In terms of educational level 24.3% had attended only elementary school, 35.4% high school, and 40% degree courses. Monthly family income (based on Brazilian minimum wage in Reais - R$ 380.00) varied between R$ 300 and R$ 999 for 23.3% of the runners, between R$ 1000 and R$ 2900 for 45.2%, and above R$ 3000 for 31.3% of them. Seventy two percent of them have been running regularly for more than 6 years, and 57% had received specialist guidance for running; 56.5% run more than 64 km/week. The injury prevalence for one year was 37.7%; BMI and waist circumference were within healthy limits. No associations were found between injury prevalence and other variables studied.